Malam Pesta Ponggal Ke-14 Sessi 1995/1996 ([S.l. : s.n.], 1996)
The programme shows Indian students cultural show in UKM.
Keywords: Universiti Kebangsaan Malaysia -- Students; East Indian -- Malaysia -- Social life and customs